2007
DOI: 10.1007/bf03325959
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of selected heavy metals in automobile soils

Abstract: AB STRACT: Studies on seasonal changes of heavy metal concentration in soils provide vital information for best management options at all times. The study investigated temporal variation in concentration of heavy metals in three towns having automobile service centres in Imo State. The study site is characterized by two major seasons in a year. Heavy metals were found in both arable and automobile soils, but more concentrations were recorded on the latter. Mean values of Cd, Cr, Ni, Hg and Pb were 6.2 mg/kg, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Soils are sandy due to their parent material origin and act as a filter (Donahue, et al, 1990) as labile Cd is leached away from the pedosphere. Soils of the study area are porous (Onweremadu, et al, 2007) and given high r ain fall amount of South eastern Niger ia (Onweremadu, 2006), the concentrations of Cd in both polluted and unpolluted soils are low as tr an slocator y pedogen ic pr ocesses, such as elviation resulted in losses in the soilsphere. However, ground-and surface-water assessment of the site was n ot conducted to ascer tain Cdconcentrations as it is suspected that lost Cd in studied soils may have caused non-point-source Cdpollution in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Soils are sandy due to their parent material origin and act as a filter (Donahue, et al, 1990) as labile Cd is leached away from the pedosphere. Soils of the study area are porous (Onweremadu, et al, 2007) and given high r ain fall amount of South eastern Niger ia (Onweremadu, 2006), the concentrations of Cd in both polluted and unpolluted soils are low as tr an slocator y pedogen ic pr ocesses, such as elviation resulted in losses in the soilsphere. However, ground-and surface-water assessment of the site was n ot conducted to ascer tain Cdconcentrations as it is suspected that lost Cd in studied soils may have caused non-point-source Cdpollution in the area.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in percent clay among the soils studied could be attributed to land use history, the intensity of cultivation. On this subject Onweremadu et al (2007) noted slight temporal textural differences in arable soils resulting from continuous (2003), very strongly acidic soils accounted for 58%, while 42% of the studied soils could be categorized as strongly acidic suggesting the presence of substantial quantities of exchangeable hydrogen and aluminum ions which are associated with acidity ( Table 2). The cation exchange capacity of the studied soils ranged from 21.15 to 36.03 cmol c kg −1 .…”
Section: Physicochemical Properties Of the Studied Soilsmentioning
confidence: 93%
“…Bulk density was significantly higher (P<0.05) in rainy season in all the studied landuse, being 1.23-1.37 g/cm 3 CCS; 1.33-1.37 g/cm 3 in FS; 1.29-1.33 g/cm 3 in POS and 1.41-1.39 g/cm 3 in BF The values of bulk density were in line with the ranges documented by Landon (1991) for tropical soils. Onweremadu et al (2007), Achmad et al (2003) and Scot et al (1994) found higher bulk densities during rainy season. Seasonal changes in bulk density are attributed to heavy annual rainfall that lasts for about 9 months and estimated to be 2500 mm thus clogging the pore spaces (Oti, 2002).…”
Section: Resultsmentioning
confidence: 88%